PENGARUH PENDAPATAN PREMI, HASIL INVESTASI DAN KLAIM TERHADAP LABA PADA PT ASURANSI MULTI ARTHA GUNA TBK (AMAG) - Amalia Ramadhani Suci Ardi; Maryam Batubara; Muhammad Ikhsan Harahap (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2022)
This study aims to determine the effect of the independent variables, namely premium income, investment returns and claims on the dependent variable, namely profits at PT Insurance Multi Artha Guna Tbk (AMAG). This study uses a quantitative methods and the data used are secondary data in the form of annual financial reports starting from 2012-2021 (last 10 years). This study uses the Eviews 10 data processing application with multiple linear regression analysis techniques. The results of this study indicate that premium income partially has a negative and insignificant effect on profits at PT Insurance Multi Artha Guna Tbk (AMAG), investment returns partially have a positive and significant effect on profits at PT Insurance Multi Artha Guna Tbk (AMAG) and claims in general partial negative and insignificant effect on profit at PT Insurance Multi Artha Guna Tbk (AMAG). Premium income, investment returns and claims simultaneously have a significant effect on profits at PT Insurance Multi Artha Guna Tbk (AMAG). Based on the coefficient of determination, profits at PT Insurance Multi Artha Guna Tbk (AMAG) is influenced by premium income, investment returns and claims of 75,8195% and the remaining 24,1805% is influenced by other factors.